Semaphorins in Angiogenesis and Autoimmune Diseases: Therapeutic Targets? - Iragavarapu-Charyulu, Vijaya; Wojcikiewicz, Ewa; Urdaneta, Alexandra (Frontiers in Immunology, 2020)
The axonal guidance molecules, semaphorins, have been described to function both physiologically and pathologically outside of the nervous system. In this review, we focus on the vertebrate semaphorins found in classes 3 through 7 and their roles in vascular development and autoimmune diseases. Recent studies indicate that while some of these vertebrate semaphorins promote angiogenesis, others have an angiostatic function. Since some semaphorins are also expressed by different immune cells and are known to modulate immune responses, they have been implicated in autoimmune disorders such as multiple sclerosis, rheumatoid arthritis, systemic lupus erythematosus and systemic sclerosis. We conclude this review by addressing strategies targeting semaphorins as potential therapeutic agents for angiogenesis and autoimmune diseases.